Anatomical and Ultrastructural Peculiarities in the Laticifers of Euphorbia antiquorum L.: A Potential Source for the Biofuel Production - Kumar, Sake Pradeep; Rajeswari, Bugude; Rao, Allu Prasada; Reddy, Lebaka Veeranjaneya; Sha Valli Khan, Patan Shaik (Current Botany, 2013)
The present study was conducted to examine the anatomy, distribution and ultrastructure of laticifer system in phylloclades of Euphorbia antiquorum L. by light and transmission electron microscopy. The phylloclade shows several anatomical characteristics well adapted to the xerophytic environment. Transverse section of E. antiquorum phylloclade displays three distinct regions namely cortical tissue, vascular cylinder and the pith region. Nonarticulated laticifers are present in three tissues, but their frequency varies with the tissue type. Highest laticifer frequency was observed in vascular cylinder (14%) followed by cortex (3.9%) and pith regions (3%). In contrast, laticifer index was greatest in the pith (9.7%) followed by vascular cylinder (6.9%) and in the cortex (4.9%). Laticifers were well recognized by the presence of nucleus and dense cytoplasm rich in ribosomes, mitochondria, plastids, endoplasmic reticulum, two types of vacuoles and osmophilic bodies when compared to the adjacent cells. Histo-chemical tests revealed the presence of phenolics, proteins, terpenoids, starch, alkaloids, indicating that this species may be useful as a potential feedstock for the production of biofuels in future from semiarid or arid environments. The discovery of laticifer system in E. antiquorum was not described earlier could also be of taxonomic value.